Identification, genetic diversity, and comparative evolution of the striped snakehead Channa striata (Bloch, 1793) in Wallacea, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Irmawati, Meimulya, Tassakka ACMAR, Nadiarti, Rukminasari N, Kadriah IAK, Nasrullah H, Alimuddin. 2022. Identification, genetic diversity, and comparative evolution of the striped snakehead Channa striata (Bloch, 1793) in Wallacea, Indonesia. Biodiversitas 23: 3327-3337. Striped snakehead, Channa striata populations have declined in some areas of Wallacea. This study aimed to identify the species, analyze the genetic diversity, and trace the evolutionary relationships of snakeheads in the Wallacea region with snakeheads in other geographic areas. This study was identifying all specimens in this study as C. striata. The Wallacean C. striata sequences comprised three haplotypes with five polymorphic sites (single nucleotide polymorphisms, SNPs). No mutations were detected in the COI nucleotides of C. striata in the Tempe Lake complex, Patampanua River, and Bojo River; therefore, they belonged to the same haplotype. The C. striata from the Tangkoli tertiary drainage had unique haplotypes that differed from other C. striata haplotypes. The intraspecific genetic distance within C. striata was low while the interspecific genetic distance within the genus Channa was quite large, indicating that mutation rates are quite high in the genus Channa. Haplotype evolution showed that C. striata in Wallacea shared a common ancestral pathway with C. striata in Kalimantan, Java, and Bali and had a different ancestral pathway with C. striata in Lampung (Sumatra). The nucleotide composition of the C. striata COI gene followed the general pattern of the Teleostei and the Pisces superclass (T>C>A>G) with the G+C base percentage lower than the A+T percentage. The data from this study will be useful as a basis for designing germplasm conservation strategies and designing strategies to maintain C. striata populations and develop strains to meet future needs.